PREVENTION OF CRYSTALLISATION OF ASPHALT-RESIN-PARAFFIN DEPOSITS UNDER THE INFLUENCE OF A PERMANENT MAGNETIC FIELD - Nalyvaiko, O.; Romashko, O.; Mitkov, V.E.; Mollova, Z. (Municipal economy of cities. Series: «Economy science», 2024)
During the operation of oil production wells, significant losses occur due to asphalt-resin-paraffin deposits (ARPD) in the pores of reservoirs and lift pipes. Understanding the detection and technology for combating ARPD is an urgent scientific, technical, and practical task, as this factor affects the wells’ operability and ultimate productivity.